EDUCATIONAL INCLUSION OF PUPILS FROM DISADVANTAGED COMMUNITIES - Enache, Rodica Gabriela; Caraion, Raluca Maria (International Journal of Legal and Social Order, 2024)
In this paper we aim to conduct a study on the implementation of educational projects and institutional partnership programs in Călărași County in order to reduce and prevent school dropout. Research objectives were the analysis of the effectiveness of educational projects and institutional partnership programs for the reduction and prevention of school dropout, at the level of Călărași county and reducing the percentage of school dropouts in educational units, from disadvantaged areas of Călăraşi County, involved in the institutional partnership projects and programs.